CHORIONIC - CARCINOMA - A CAUSE OF REPEATED HYDROPSY IN A DAIRY BUFFALO - SINGH, A K; BRAR, P S; SANDHU, B S; SOOD, N K (The Indian Journal of Animal Reproduction, 2023)
A case of repeated hydropsy due to chorio-carcinoma in a dairy buffalo is described.
Keywords: Buffalo; Chorionic - carcinoma; Hydropsy